An Improved Error Analysis for Finite Element Approximation of Bioluminescence Tomography (Journal of Computational Mathematics, 2018)
This paper is concerned with an ill-posed problem which results from the area of molecular imaging and is known as BLT problem. Using Tikhonov regularization technique, a quadratic optimization problem can be formulated. We provide an improved error estimate for the finite element approximation of the regularized optimization problem. Some numerical examples are presented to demonstrate our theoretical results.
Keywords: BLT problem; Tikhonov regularization; Optimization problem; A priori error estimate.